Sikap Pemerintah Ponorogo Dalam Pemberian Efek Jera Terhadap Masyarakat Pasca Uji Coba “New Normal” - Alfi Dwi Krismaroca; Robby Darwis Nasution (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2021)
At present the term of New Normal has spread to various element of society, and is existence is a subject of serious discussion. The government and society are equally aware that New Normal is a new lifestyle in the pandemic Covid-19 era which aims ro revive the center of economi, business, and social interaction between society in various regions. New Normal at it’s essence is to require people to conform, also in accordance with health protocols. Anywhere based on the Covid-19 pandemic era ends. Ponorogo is one of the district that has used the New Normal national discourse as a concept to be tested. But after it is implemented, it is found that there are still many people who are not aware and take care of themselves by not wearing masks when traveling. This phenomenon certainly triggers serious concern, so tis research seeks to provide a description through collecting valid data and supported by relevant theories as a narrative reinforcement. Many society who still violate also indicates the extent to which the effectiveness and efforts of the Ponorogo government so far has been conducting socialization and education about the dangers of Covid-19 and ways to counter it